Muhammad and the Christian: By Kenneth Cragg, (Maryknoll, N.Y., Orbis Books, 1984.) $8.95 pp. 180. (American Journal of Islam and Society, 1985)
Muslim-Christian dialogue is an area in which Muslim interest and involvement has increased as greater numbers of Muslims have come to the West and settled and interacted with local populations. From the Muslim point of view the early dialogues with Christian missionaries in the colonial period largely consisted of apologetic reactions and defences against attacks on Islamic beliefs and practices. Today dialogue, at least in some areas, allows a sharing by participants of their respective ideals and world views in search of a common ground for peaceful co-existence and mutual respect. Since Islamic theology incorporates a position on the status of other religions which is based on the Qur'an, it is both more easy and in some ways more difficult for Muslims to dialogue with their neighbors. The broad themes of salvation and righteousness are clearly articulated, and it is the more specific issues which may remain points of contention. Those interested in Christian-Muslim dialogue may wish to examine a recent work Muhammad and the Christian by Kenneth Cragg, an Anglican Bishop who knows Arabic and is the author of a number of books on Islam. In this work, speaking as a Christian, Cragg attempts to formulate an appropriate "positive" Christian response to Prophet Muhammad and the Qur'an. In nine chapters. the major topics of which are usefully summarized in the table of contents, the author addresses themes such as: the role of Prophet Muhammad in history, the Islamic understanding of Muhammad, the role of the Sunna, and the contents of the Qur'an. The author focuses primarily on Islamic understandings of God and the Prophet rather than on traditional fields of Muslim/Christian controversy such as the divinity of Jesus, the Trinity, the crucifixion, and so on. It is a work for those already knowledgeable about each religion since many complex points of faith are raised and discussed, occasionally with a subtlety verging on abstruseness. On the positive side, although the book is primarily addressed to the Christian reader, the Muslim who reads Cragg's reflections will at certain points be moved to reflect more deeply on the existential ...